2005
DOI: 10.4028/www.scientific.net/amr.6-8.705
|View full text |Cite
|
Sign up to set email alerts
|

Size-Effects in Micro-Metal Sheet Forming of Unalloyed Copper and Brass

Abstract: Micro-metal forming technologies are mass production methods, net shape forming, low-cost procedures and quality controlled processes. Its scale region is in the range of the margin area between conventional precision manufacturing and silicon-based technology. The first paper to study the field of micro metal forming was written in 1989. Up to now, there have been many papers in this field but the results of the experiments do not reach the same conclusions. It should be noted that it is not possible to apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Tensile, bending and upsetting tests have been carried out to investigate the size effect on aluminium, copper and brass material. 12,16 It was found that flow stress decreases with scaling down of the size of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile, bending and upsetting tests have been carried out to investigate the size effect on aluminium, copper and brass material. 12,16 It was found that flow stress decreases with scaling down of the size of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al [6] used two kinds of copper alloy C12000 and C26000 for micro forging and micro tensile test respectively in 2005, and compared the difference in size effect between these two testing processes. The experiment results show that C26000 has better matrix strength and grain strength.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, comprehensive tests and investigations of various materials in the micro scale region are required to obtain the basic and fundamental knowledge of size effect for micro forming. Tsai et al [4] conducted tensile and upsetting tests on C12000 copper and C26000 brass to understand the size effects. Miyazaki [5] selected different materials to investigate the size effect on the flow stress curve with various grain sizes and specimen thicknesses.…”
Section: Introductionmentioning
confidence: 99%